Domesticating dragons - Koboldt, Dan (Daniel C.) (Koboldt, Dan (Daniel C.). Reptilian Corp, 2021)
Noah Parker, a newly minted PhD, is thrilled to land a dream job at Reptilian Corporation, the hottest tech company in the American Southwest. He's eager to put his genetic engineering expertise to use designing new lines of Reptilian's feature product: living, breathing dragons. Although highly specialized dragons have been used for industrial purposes for years, Reptilian is desperate to crack the general retail market. By creating a dragon that can be the perfect family pet, Reptilian hopes to put a dragon into every home. While Noah's research may help Reptilian create truly domesticated dragons, Noah has a secret goal. With his access to the company's equipment and resources, Noah plans to slip changes into the dragons' genetic code, bending the company's products to another purpose entirely . . .